Role of maternal cortisol hormone on gene regulation of zebrafish (Danio rerio, F. Hamilton, 1822) - Rabbane, Md Golam; Rahman, Mohammad Shamsur; Hossain, Anwar (Dhaka University Journal of Biological Sciences, 2013)
This study was conducted to investigate the role of cortisol, a steroid hormone on the gene expression during embryogenesis of zebrafish (Danio rerio). Gene expression analyses were performed using microarray hybridization. A total 80 genes were found to be up-regulated and 36 genes were down-regulated at 24 hrs post fertilization (hpf) when the fertilized eggs were treated with cortisol hormone. These findings suggest that substantial changes in the responsiveness to maternal cortisol may occur at early developmental phase. Dhaka Univ. J. Biol. Sci. 22(2): 135-144, 2013 (July)